(untitled) (Bangladesh Journal of Medical Biochemistry, 2018)
The oral contraceptive pill fulfills the great human need for birth control with unrivalled effectiveness. The pill can effectively prevent pregnancy and alleviate menstrual disorder when used correctly. Many biochemical profiles of women taking oral contraceptives are disturbed due to metabolic alterations induced by its hormone content. The study was carried out in the Department of Biochemistry, Mymensingh Medical College, Mymensingh, during the period of July 2016 to June 2017 to evaluate the status of serum calcium and magnesium in oral contraceptive user women. For this study, 120 age-matched women were selected and grouped as 60 oral contraceptive user women and 60 non-oral contraceptive user women. Data were analyzed with the help of SPSS version 21. Mean±SD level of serum calcium and magnesium were 9.50±0.70 mg/dl and 1.81±0.13 mg/dl in oral contraceptive user women, while in normal healthy women the levels were 9.03±1.69 mg/dl and 2.10±0.17 mg/dl respectively. No significant difference of serum calcium between two groups was observed (p>0.05). Serum magnesium significantly reduced in oral contraceptive users when compared with non-oral contraceptive users (p<0.001). The study showed no significant difference in serum calcium level in contraceptive group when compared with noncontraceptive user group and serum magnesium level was significantly reduced in oral contraceptive users when compared to normal healthy group. Bangladesh J Med Biochem 2017; 10(2): 64-68